PENGARUH ABSENSI SIDIK JARI DAN UANG MAKAN TERHADAP KINERJA GURU RUMPUN PAI DI MTS NEGERI 2 KOTA BENGKULU - Siti Halina (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This research  started  from the problem  of giving of food money  which is paid based  on the attendance of civil ser- vant in working day, hence  giving of food money  can only be done  if recapitulation of civil servant  attendance for one month. This study aims to (1) to determine whether  there  is a significant and  positive influence of fingerprint attendance variable  and money  meal  variable  against  teacher  performance variable  PAI in MTs Negeri 2 Kota Bengkulu.  The research  method used survey  method, questionnaire data  collection  technique and  documentation. Data  analysis  techniques used  in this study  is to use multiple linear regression  analysis.  Data  were collected,  processed and  analyzed  using SPSS  version  16.0.  The results showed  that (1) From  the partial  test result (t test) shows the probability  significance (sig) of 0.031  <0.05, meaning that the fingerprint attendance significantly influences the performance of the PAI teacher  is accepted. (2) From the partial test shows the probability of significance (sig) of 0.000  <0.05, meaning that the influence of the meal significantly influence the performance of PAI teacher  group  is accepted (3) From the simultaneous test results (Test F) shows sig probability.  Fchange is 0.000.  Since the Fchange value is less than  0.05  (0.05),  thus fingerprint and  fingerprint attendance significantly influence the PAI teacher’s performance is acceptable. Based on the value of R2 (R Square), the value of 0.993  is equal to 93%, meaning that the effect of fingerprint attendance and  teacher’s  meal money  on teacher  performance of PAI family is high, and  the rest 7% is influenced by other factors not examined.